Percepcja życzliwości w środowisku szkolnym z perspektywy uczniów o różnej tożsamości płciowej - Cwojdzińska, Anna; Szafran, Joanna (Studia Edukacyjne, 2025)
The analyses presented were to verify whether students’ experiences of kindness at school differ depending on their gender identity. The key findings indicate significant differences in the perception of kindness. Students who do not identify within binary gender categories are more likely than their peers to perceive the school environment as uncaring. The study suggests that current school environments may not sufficiently recognize and address the emotional and social needs of all students, particularly those at risk of exclusion. The article emphasizes the importance of kindness as a means of promoting inclusion and preventing gender-based inequalities in the school environment. The findings underscore the necessity of implementing targeted, kindness-based interventions and providing teacher training to foster more supportive educational communities.